2015
DOI: 10.1002/pon.4044
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial oncology care resources in Europe: a study under the European Partnership for Action Against Cancer (EPAAC)

Abstract: Background: Cancer is a complex health problem requiring multidisciplinary care. There are clinical guidelines available in order to improve the process and outcomes of cancer care within Europe. However, strategic action is still needed in many European Union (EU) Member States to develop or improve national cancer control plans (NCCPs), which play a key role in cancer control and care. The current study clarifies the extent of implementation of psychosocial oncology care (PSOC) in the EU.Method: A survey met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 24 publications
0
44
0
4
Order By: Relevance
“…In Europe, a recent survey conducted under the European Partnership on Action Against Cancer and involving 27 representatives of European countries showed that only 8 (30%) reported having nationally recommended psychosocial oncology care (PSOC) clinical guidelines, with 10 (37%) having specific budgets for PSOC, and 6 (22%) having an official certification for PSOC education …”
Section: Introductionmentioning
confidence: 99%
“…In Europe, a recent survey conducted under the European Partnership on Action Against Cancer and involving 27 representatives of European countries showed that only 8 (30%) reported having nationally recommended psychosocial oncology care (PSOC) clinical guidelines, with 10 (37%) having specific budgets for PSOC, and 6 (22%) having an official certification for PSOC education …”
Section: Introductionmentioning
confidence: 99%
“…Lack of time and resources, inadequate interdisciplinary communication and cooperation, limited knowledge of and familiarity with psychosocial well-being and care options were found to be barriers for HCP to integrate the psychosocial approach in routine care (Dilworth, Higgings, Parker, Kelly, & Turner, 2014;Fagerlind, Kettis, Glimelius, & Ring, 2013;Wei et al, 2017). As found in the study of Travado, Reis, Watson, and Borras (2015), HCP feel that the existing financing system of cancer care and the (lack of) coordination in the psychosocial approach induce thresholds. Nurses could, for example, have a more explicit role in detecting, working with and referring for psychosocial needs of cancer patients, integrated in a multidisciplinary team approach (Ercolano, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of psychosocial oncology as a discipline and the implementation of international standards[17] of cancer care will take much hard and sustained work as well as both human and financial resources. Cancer care professionals need to work with all professional, political, and business communities to conduct research and disseminate the benefits of psychosocial care to patients, institutions, and governments.…”
Section: Cancer Care Todaymentioning
confidence: 99%